High Glass Transition Epoxy Resins from Biobased Phloroglucinol and Unmodified Kraft Lignin - Janesch, Jan; Dinu, Roxana; Rosenau, Thomas; Potthast, Antje; Gindl-Altmutter, Wolfgang; Grasböck, Stefan; Sulaeva, Irina; Mija, Alice (ACS omega, 2025)
This study investigates the development of high-performance epoxy resins derived from potentially biobased phloroglucinol triglycidyl ether (TGPh) and unmodified Kraft lignin (KL), aiming to create thermoset materials from renewable resources. Two types of KL, sourced from hardwood and softwood, were incorporated into the TGPh matrix at high loadings of 30% wt. to achieve materials with potentially ∼95% renewable content. The resulting epoxy resins were characterized using thermally resolved Fourier-transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), dynamic mechanical analysis (DMA), tensile testing, and scanning electron microscopy (SEM). All samples exhibited >97% gel content after 3 days in various solvents, indicating complete cross-linking. DSC and FTIR analyses confirmed the interaction of KL with the resin, suggesting that lignin may act as a cohardener. The addition of lignin increased the glass transition values (T g) from 146 °C for the pure TGPh homopolymer to 178 and 187 °C for TGPh cured with softwood and hardwood KLs, respectively, indicating an increased cross-link density. Although the tensile strength of the resins decreased from 51.1 ± 16.0 MPa (mean ± SD) for the TGPh homopolymer to approximately 20.0 ± 2.8 MPa (mean ± SD) and 16.3 ± 2.3 MPa (mean ± SD) for the TGPh thermosets obtained with softwood and hardwood KLs, respectively, the stiffness was maintained at a tensile modulus of 2–2.5 GPa. SEM analysis revealed inhomogeneities in the lignin-containing samples, potentially explaining their lower mechanical properties. The findings demonstrate the potential of these biobased epoxy resins, particularly for applications such as electronics, automotive, and aerospace, which require high glass transition temperatures. Moreover, the results help in understanding the active action of lignin in the cross-linking of epoxy resins.